Fluorescent nanosensors for intracellular measurements: synthesis, characterization, calibration, and measurement - Desai, Arpan S.; Chauhan, Veeren M.; Johnston, Angus P.; Esler, Tim; Aylott, Jonathan W. (Frontiers in Physiology, 2014)
Measurement of intracellular acidification is important for understanding fundamental biological pathways as well as developing effective therapeutic strategies. Fluorescent pH nanosensors are an enabling technology for real-time monitoring of intracellular acidification. The physicochemical characteristics of nanosensors can be engineered to target specific cellular compartments and respond to external stimuli. Therefore nanosensors represent a versatile approach for probing biological pathways inside cells. The fundamental components of nanosensors comprise a pH-sensitive fluorophore (signal transducer) and a pH-insensitive reference fluorophore (internal standard) immobilised in an inert non-toxic matrix. The inert matrix prevents interference of cellular components with the sensing elements as well as minimizing potentially harmful effects of some fluorophores on cell function. Fluorescent nanosensors are synthesised using standard laboratory equipment and are detectable by non-invasive widely accessibly imaging techniques. The outcomes of studies employing this technology are dependent on reliable methodology for performing measurements. In particular special consideration must be given to conditions for sensor calibration, uptake conditions and parameters for image analysis. We describe procedures for: 1) synthesis and characterisation of polyacrylamide and silica based nanosensors 2) nanosensor calibration and 3) performing measurements using fluorescence microscopy.